2011
DOI: 10.1021/cm2011617
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Responsive Liquid Crystalline Monomers and Polymers

Abstract: b S Supporting Information ' INTRODUCTIONSmall molecule and polymeric liquid crystalline materials have applications in a multitude of areas, ranging from displays, optical/ electronic imaging, data storage, and stress/temperature sensing to chemical/fire resistance and artificial muscle actuation. 1 The design of typical molecular architectures that facilitate thermotropic liquid crystalline behavior is well documented. Molecules with structural anisotropy, i.e., a rigid moiety with high aspect ratio are fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 87 publications
0
34
0
1
Order By: Relevance
“…[2] A statistical mechanics (Ising model) analysis suggests that standard repulsive nearest neighbor intermetallic interactions operating in linear polymers with regularly spaced binding sites should provide the targeted ordered …-Ln 1 -Ln 2 -Ln 1 -Ln 2 -… microstates. [3,4] Pioneering work in this field has relied on the bulk electropolymerization of didentate 1,10-phenanthroline with thienyl spacers [5] and the acyclic diene metathesis of tridentate 2,6-bis(benzimidazol-2-yl)pyridine, [6] followed by reaction with Eu(β-diketonate) 3 or Eu(NO 3 ) 3 to yield red-emitting metallopolymers. A reliable exploitation of this concept for the development of luminescent materials, however, requires the efficient sensitization of the luminophore via the rational optimization of each photophysical step by using chemical tools.…”
mentioning
confidence: 99%
“…[2] A statistical mechanics (Ising model) analysis suggests that standard repulsive nearest neighbor intermetallic interactions operating in linear polymers with regularly spaced binding sites should provide the targeted ordered …-Ln 1 -Ln 2 -Ln 1 -Ln 2 -… microstates. [3,4] Pioneering work in this field has relied on the bulk electropolymerization of didentate 1,10-phenanthroline with thienyl spacers [5] and the acyclic diene metathesis of tridentate 2,6-bis(benzimidazol-2-yl)pyridine, [6] followed by reaction with Eu(β-diketonate) 3 or Eu(NO 3 ) 3 to yield red-emitting metallopolymers. A reliable exploitation of this concept for the development of luminescent materials, however, requires the efficient sensitization of the luminophore via the rational optimization of each photophysical step by using chemical tools.…”
mentioning
confidence: 99%
“…Nowadays, many research teams concentrate their attention on exploiting metal-ligand coordination to construct metallosupramolecular polymers [48][49][50][51] with reversibility in response to external stimulus, such as redox or light.…”
Section: Metal-ligand Coordinationmentioning
confidence: 99%
“…[2] A statistical mechanics (Ising model) analysis suggests that standard repulsive nearest neighbor intermetallic interactions operating in linear polymers with regularly spaced binding sites should provide the targeted ordered …-Ln 1 -Ln 2 -Ln 1 -Ln 2 -… microstates. [3,4] Pioneering work in this field has relied on the bulk electropolymerization of didentate 1,10-phenanthroline with thienyl spacers, [5] and the acyclic diene metathesis of tridentate 2,6-bis(benzimidazol-2-yl)pyridine, [6] followed by reaction with [Eu(b-diketonate) 3 ] or Eu(NO 3 ) 3 to yield red-emitting metallopolymers. A reliable exploitation of this concept for the development of luminescent materials, however, requires the efficient sensitization of the luminophore through the rational optimization of each photophysical step by using chemical tools.As a first step toward this goal, the rigid segmental ligand strands L1-L3, made of two tridentate binding units separated by a rigid and electronically tunable aromatic spacer, have been treated with trivalent europium to give the dinuclear complexes [Eu 2 (L)(hfac) 6 ] (Scheme 1; hfac = hexafluoroacetonato).…”
mentioning
confidence: 99%
“…As a first step toward this goal, the rigid segmental ligand strands L1-L3, made of two tridentate binding units separated by a rigid and electronically tunable aromatic spacer, have been treated with trivalent europium to give the dinuclear complexes [Eu 2 (L)(hfac) 6 ] (Scheme 1; hfac = hexafluoroacetonato). [7] The use of a simple method for deciphering the various contributions to the sensitization mechanism clearly showed that [Eu 2 (L3)(hfac) 6 ] had the largest global emission quantum yield [F L Eu = 0.206 (7), Eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation